Oral health of patients suffering from end-stage solid organ insufficiency prior to solid organ re-transplantation: a retrospective case series study - Möst, Tobias; Lutz, Rainer; Jahn, Arne Eric; Heller, Katharina M.; Schiffer, Mario; Adler, Werner; Deschner, James; Weber, Manuel; Kesting, Marco Rainer (BMC Oral Health, 2021)
Background: The oral health of organ transplanted patients before organ re-transplantation is largely unknown. This retrospective clinical study evaluates the necessity for intraoral surgical intervention and/or conservative treatment in candidates awaiting organ re-transplantation, both for graft failure and for reasons of another upcoming solid organ transplantation (renal or non-renal). Methods: From January 2015 to March 2020 n = 19 transplant recipients in evaluation on the waiting list for solid organ re-transplantation could be included in the retrospective case series study. Using clinical and radiological examinations, necessity for oral surgical or conservative dental treatment was evaluated. On the basis of anamnesis data, current kidney function, renal replacement treatment (RRT), and medication, a risk profile for several patient subgroups was created. Results: The clinical and radiological examinations showed a conservative and/or surgical treatment need in n = 13 cases (68.42%). In n = 7 cases (36.84%) surgical intervention was recommended due to residual root remnants (n = 5), unclear mucosal changes (n = 1), and periimplantitis (n = 1). In n = 16 recipients (84.2%) RRT (n = 15 hemodialysis; n = 1 peritoneal dialysis) had been performed. N = 14 recipients (73.68%) received immunosuppressants. In n = 1 patient (5.3%) displayed intraoral and n = 4 patients (21.1%) extraoral neoplasms due to drug-induced immunosuppression. Conclusions: Solid organ transplant recipients with renal failure present a complex treatment profile due to a double burden of uremia plus immunosuppressants. In cases of surgical treatment need a hospitalized setting is recommended, where potentially necessary follow-up care and close cooperation with disciplines of internal medicine is possible in order to avoid surgical and/or internal complications.
CRIS-Team Scopus Importer:2021-11-05
Keywords: Immunosuppression; Oral health; Organ transplantation